Common genetic causes of holoprosencephaly are limited to a small set of evolutionarily conserved driver genes of midline development coordinated by TGF‐β, hedgehog, and FGF signaling. Issue 10 (26th July 2018) - Roessler, Erich; Hu, Ping; Marino, Juliana; Hong, Sungkook; Hart, Rachel; Berger, Seth; Martinez, Ariel; Abe, Yu; Kruszka, Paul; Thomas, James W.; Mullikin, James C.; ,; et al.
Abstract: Here, we applied targeted capture to examine 153 genes representative of all the major vertebrate developmental pathways among 333 probands to rank their relative significance as causes for holoprosencephaly (HPE). We now show that comparisons of variant transmission versus nontransmission among 136 HPE Trios indicates some reported genes now lack confirmation, while novel genes are implicated. Furthermore, we demonstrate that variation of modest intrinsic effect can synergize with these driver mutations as gene modifiers. Abstract : Next‐generation sequencing allows for simultaneous interrogation of entire developmental pathways whose interactions between driver genes, modifying factors, epigenetic signatures, transcriptional responses, and environmental exposures can be ultimately integrated into variable phenotypic effects. This work demonstrates that the genetic basis underlying the malformation sequence of the forebrain, holoprosencephaly, is much simpler than previously appreciated and involves a small number of driver genes. Each of these driver genes participates in a highly conserved program, thus linking them into an intelligible pathogenic scheme.